2020
DOI: 10.1111/sms.13610
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and methodological perspectives on the impact of intense interval training on post‐exercise metabolism

Abstract: The post‐exercise recovery period is associated with an elevated metabolism known as excess post‐exercise oxygen consumption (EPOC). The relationship between exercise duration and EPOC magnitude is thought to be linear whereas the relationship between EPOC magnitude and exercise intensity is thought to be exponential. Accordingly, near‐maximal and supramaximal protocols such as high‐intensity interval training (HIIT) and sprint interval training (SIT) protocols have been hypothesized to produce greater EPOC ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 92 publications
(339 reference statements)
2
48
0
1
Order By: Relevance
“…24 Indeed, the greater elevation of post-exercise EE was deemed as one of potential contributors to the promising effects of HIIT and SIT interventions on fat loss. 25 It has been shown that a single session of SIT could induce an elevation of daily EE of >225 kcal, 26 markedly greater than that mediated by the MICT counterparts. 25 The elevated post-exercise EE following vigorous exercise, which is likely a consequence of the restoration of physiological equilibrium from the exercise-mediated metabolic perturbations, appears to be relied on fat oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…24 Indeed, the greater elevation of post-exercise EE was deemed as one of potential contributors to the promising effects of HIIT and SIT interventions on fat loss. 25 It has been shown that a single session of SIT could induce an elevation of daily EE of >225 kcal, 26 markedly greater than that mediated by the MICT counterparts. 25 The elevated post-exercise EE following vigorous exercise, which is likely a consequence of the restoration of physiological equilibrium from the exercise-mediated metabolic perturbations, appears to be relied on fat oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…In general, huddling behavior completely or partially alleviated the increase in glycogen content caused by the increase in glycogen synthesis in the myocardium of voles following cold environment exposure. Normal glycogen metabolism is the basis of exercise in mammals [39,40]. Earlier studies on Brandt's voles showed that activity is higher in huddling groups than separated groups under cool environments [19].…”
Section: Discussionmentioning
confidence: 99%
“…9 Fat oxidation could be facilitated by a higher oxygen consumption observed after exercises performed at an intensity above 75% of VO 2max . 14,15 Therefore, using a randomized crossover design, we compared the 2 hours post-exercise VO 2 and fat utilization after three isoenergetic exercise sessions (MICE, and two HIIE with different active phase duration but at the same intensity). The first one [60 × (8-s cycling − 12-s recovery) at 80%-90% HR max ] has been extensively tested by our group and by others in pre-and post-menopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…9 These adaptations are probably facilitated by the higher excess post-exercise oxygen consumption (EPOC) generally observed after exercise performed above 75% of the maximal oxygen uptake (VO 2max ). 14,15 Moreover, a decrease of post-exercise appetite could also contribute to the larger fat mass loss. 9 Indeed, acute high-intensity intermittent exercise (HIIE) may stimulate anorexigenic signals that could limit energy intake for few hours.…”
mentioning
confidence: 99%